2018
DOI: 10.1089/end.2017.0714
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Simple Prostatectomy by an Extraperitoneal Approach

Abstract: The incidence of symptomatic benign prostate hyperplasia and bladder outlet obstruction has increased during the last two decades. Most of men are treated conservatively. When medical therapy is inadequate to relief symptoms, surgical treatment is necessary. Absolute indications for surgical treatment are gross hematuria, recurrent urinary infections and retentions as well as bladder stones. With advent of minimally invasive surgery, large prostates tend to be treated either endoscopically or laparoscopically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As a minimal invasive alternative to OSP, robot-assisted simple prostatectomy (RASP) was first described by Sotelo et al in 2008 [4]. Since then, different transperitoneal and extraperitoneal approaches have been developed [5][6][7]. Efficacy and safety of RASP have been investigated in different noncomparative studies and a multinational analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As a minimal invasive alternative to OSP, robot-assisted simple prostatectomy (RASP) was first described by Sotelo et al in 2008 [4]. Since then, different transperitoneal and extraperitoneal approaches have been developed [5][6][7]. Efficacy and safety of RASP have been investigated in different noncomparative studies and a multinational analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several centers worldwide have reported small case series with perioperative and functional results similar to HoLEP and OP. [ 16 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] [ Table 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…Our mean pathology specimen weight was 82.8 g, with other series reporting between 46 g and 162 g on an average. [ 16 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] “Trifecta” arbitrarily included (a) no perioperative complications, (b) postoperative IPSS <8, and (c) postoperative Qmax > 15 ml/s. [ 27 ] Although it needs external validation, many researchers[ 27 38 ] recognized that this might be a simple way to define successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical technique of RSP essentially reproduces OSP, with the principal difference being that the basic approach of RSP is transperitoneal. Recently, however, Stolzenburg et al [15] reported a case of RSP using an extraperitoneal approach. There are 2 ways to resect an adenoma: the transvesical approach and the transcapsular approach.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The preperitoneal space is prepared with finger dissection and balloon insufflation. After all trocars are inserted, a cystotomy incision is made longitudinally from the anterior bladder wall to the bladder neck, and the adenoma is removed in a similar way as in the transperitoneal approach [15].…”
Section: Extraperitoneal Approachmentioning
confidence: 99%